Efficacy of calcium excretion and calcium/creatinine clearance ratio in the differential diagnosis of familial hypocalciuric hypercalcemia and primary hyperparathyroidism. Issue 5 (15th December 2018) - Bhangu, Jagdeep Singh; Selberherr, Andreas; Brammen, Lindsay; Scheuba, Christian; Riss, Philipp
Abstract: Background: Twenty‐four‐hour renal calcium‐excretion (CE) and calcium/creatinine‐clearance‐ratio (CCCR), respectively, are widely used to rule out familial hypocalciuric hypercalcemia (FHH) in patients with suspected primary hyperparathyroidism before surgery. The aim was to evaluate the practicability of CE compared to CCCR. Patients and Methods: We analyzed biochemical parameters, surgical treatment, gene mutation results, and long‐term follow‐up data of 198 patients (including 14 patients with FHH) and the discriminative power of CE and CCCR. Results: Twenty four patients (12.1%) had a low CE and 35 patients (20.2%) had a CCCR indicating FHH. However, eight patients with FHH (57.1%) had a normal or increased CE. Correspondingly, only eight cases of FHH (57.1%) were correctly predicted by CCCR. Sensitivity/specificity were 42.9%/89.9% for CE and 64.3%/79.9% for CCCR, showing no statistical differences ( P  = 0.482) between both methods. Conclusion: Neither CE nor CCCR was able to distinguish between PHPT and FHH but may help to narrow down potential FHH patients.